If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -1b = 6 Solving 3a + -1b = 6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. 3a + -1b + b = 6 + b Combine like terms: -1b + b = 0 3a + 0 = 6 + b 3a = 6 + b Divide each side by '3'. a = 2 + 0.3333333333b Simplifying a = 2 + 0.3333333333b
| 4x-2(-1)=4x-23(-5) | | y=3x+8-(12x) | | 81x^2=100x | | 15a^2-8=29a+6 | | 3264/5.10 | | 3x-2h=46 | | 6x+10+3x=118 | | 3n^2+12n-63=0 | | -4j+j= | | 4(2+8v)=-6v+8 | | 1a+3b=6 | | 6s+-8=18 | | (2x+4)(3x-3)=0 | | x-2.4=5.6 | | 3x^3+87x^2+162x=0 | | 5x+1-18= | | (7x+15)+(x+5)=180 | | .25(8-6x+12)= | | 15a^2-8=29a+9 | | 2x^3-21x^2+34x=0 | | 8x^3-3x^2-32x+12=0 | | 10+3x+2x=-45 | | 9+2y=y | | 9(x-1)=6(x+5) | | (3+w)w=w(7-w) | | 5j-j=12 | | x^2-50x+100=8400 | | 6x^3+26x^2-76x=0 | | 9-(w+4)=-10 | | 2x-6-2(2x+8)3=4x+1 | | 3.5x=9 | | .1x-.9x^2=0 |